Children's Whining in Family Interaction. Issue 1 (2nd January 2018) - Butler, Carly W.; Edwards, Derek
ABSTRACT: Children's whining is identified in extracts of video-recorded social interaction at home with siblings, parents, and other family. "Whining" is primarily a vernacular category, but it can be identified in terms of a set of phonetic features including pitch movement, loudness and nasality, and contrasted with crying. We focus on the uses and consequences of whining, in and for social interaction. Rather than identifying and attributing experiential causes or correlates of whining, we examine what children do with it, how it is occasioned, and how others, mostly parents, respond to it. Whining performs actions such as objecting to transgressions and thwarted goals and making complaints. Parental reactions include one or more of: "stance inversion, " which is the adoption of a contrasting tone in next turn; formulations of the offending circumstances; orientations to remedying the problem; and rejection of the whine's basis, including dispositional formulations of the child's whining (e.g., being "grumpy") and accounts for not complying with a called-for remedy. Data are in English.